Processos de adoecimento: experi??ncias vividas por professores no exerc??cio profissional - Oliveira, Rosemary Gon??alves de (2017)
The present study aims to search the experiences of teachers of municipal public basic education diagnosed with some mental and behavioral disorder, with the objective of identifying / analyzing common elements. The complex thinking in Edgar Morin's perspective was the theoretical reference of this dissertation since in the sickness by mental and behavioral disorders is the combination of biological, psychological and social factors that makes it a complex phenomenon. It makes a qualitative approach with open interviews to five primary and final elementary school teachers from four different municipalities in the state of S??o Paulo. Objective and subjective aspects intrinsic to the subject and school environment are observed in the reports of teachers' experiences. It obtained as results the following common elements in the experiences: the choice of the profession; the relationships established in the interactions with students and their families, with co-workers and with school management; the lack of support in situations of violence experienced daily. The analyzes of these elements indicate the need to rethink the relationships for an ethics of understanding the human condition, educational and health policies in the work environment that considers the subject in his actions, as well as the inclusion of education to the understanding of the condition In initial teacher education and education professionals in general. For future research, it also aims to listen to others involved in the educational process, such as managers, students and their families, in the search for a joint understanding of the school educational process.